Process Generated Contaminants (Czech Journal of Multidisciplinary Innovations, 2022)
During the technological process of PP production, chemical reactions occur, resulting in the formation of desirable and undesirable products. Some of these undesirable compounds may exhibit toxic effects. The number of compounds formed is still unknown, but a large number of them have already been identified as polynuclear aromatic hydrocarbons, heterocyclic amines, nitrosoamines, oxidized styrenes, lysinesolamines, etc. acrylamide has recently been identified as a still unknown contaminant. Thanks to this discovery, it became clear that other toxicological substances, like still unknown compounds, are likely to be formed during food production [1,2,3]. In this article, we intend to consider in most detail only three compounds or classes of compounds.